Pengaruh Manajemen Resiko Terhadap Kinerja Keuangan Perbankan Di Indonesia - Bayu Adi Bahtiar; Clarita Intari Citra Dewi; Della Yolanda; Agus Eko Sujianto (Populer: Jurnal Penelitian Mahasiswa, 2023)
There is a goal to be achieved in this research, namely to determine the effect of risk management on the financial performance of banks in Indonesia. One of the factors that influence banking financial performance is risk. There is a goal to be achieved in this study, namely to determine the effect of credit risk (NPL) and market risk (NIM) on the financial performance of banks in Indonesia. The sample used in this study is banking financial performance for 3 years which is calculated from 2016 to 2019. In this study the analytical method used is multiple linear regression analysis. The results of the study show that NPL has a negative and significant effect on banking financial performance. Meanwhile, NIM has a significant positive effect on ROA.